Over-investigation and overtreatment in pediatrics: a survey from the European Academy of Paediatrics and Japan Pediatric Society - Jankauskaite, Lina; Wyder, Corinne; del Torso, Stefano; Mamenko, Marina; Trapani, Sandra; Grossman, Zachi; Hadjipanayis, Adamos; Geitmann, Karin; Matsui, Hikoro; Saitoh, Akihiko; Isayama, Tetsuya; Karara, Nora; et al. (Frontiers in Pediatrics, 2024)
Avoiding over-investigation and overtreatment in health care is a challenge for clinicians across the world, prompting the international Choosing Wisely campaign.Lists of recommendations regarding medical overactivity are helpful tools to guide clinicians and quality improvement initiatives. We aimed to identify the most frequent and important clinical challenges related to pediatric medical overactivity in Europe and Japan. Based on the results, we aim to establish a (European) list of Choosing Wisely recommendations.In an online survey, clinicians responsible for child health care in Europe and Japan were invited to rate 18 predefined examples of medical overactivity. This list was compiled by a specific strategic advisory group belonging to the European Academy of Paediatrics (EAP). Participants were asked to rate on a Likert scale (5 as the most frequent/important) according to how frequent these examples were in their working environment, and how important they were considered for change in practice.Of 2716 physicians who completed the survey, 93% (n=2524) came from 17 countries, Japan (n=549) being the largest contributor. Pediatricians or pediatric residents comprised 89%, and 51% had 10-30 years of clinical experience.Cough and cold medicines, and inhaled drugs in bronchiolitis were ranked as the most frequent (3.18 and 3.07 on the Likert scale, respectively), followed by intravenous antibiotics for a predefined duration (3.01), antibiotics in uncomplicated acute otitis media (2.96) and in well-appearing newborns. Regarding importance, the abovementioned five topics in addition to two other examples of antibiotic overtreatment were among the top 10. Also, IgE tests for food allergies without relevant medical history and acid blockers for infant GER were ranked high.Overtreatment with antibiotics together with cough/cold medicines and inhaled drugs in bronchiolitis were rated as the most frequent and important examples of overtreatment across countries in Europe and Japan.